Relationship Between High Sodium Chloride Intake and Obesity in Hypertensive Population A Cross-Sectional Study - Muhammad Nauman Shahid, Khawaja Allah Ditta Saad, Alizea Fatima Sherazi, Dania Zubair, Maryam Faseeh, Syed Mohammad Murtaza, (Pakistan Journal of Medical & Health Sciences, 2023)
Background: High Sodium chloride intake and obesity are significant, regarding hypertension in the population which may develop several medical complications. Objective: The aims and objectives of the current study were to introduce lifestyle medicine awareness in people for managing high blood pressure caused by high sodium chloride intake and obesity. Study Design: It was a cross-sectional clinical Study of the management of high blood pressure in a population with the help of nutrition & physical exercise. Place and Duration: The present study was conducted from January to May 2023 and Patients were selected from the community health center and Ghurky Hospital Lahore. Methodology: ToA total of 10 of 0 hypertensive individuals were selected and divided into different groups regarding hypertension, obesity, sodium chloride intake in daily life, and other demographics. People were separated into different groups based on their sodium intake levels and BMI people were separated into different groups. In group- A there was 50 male and female while in group B other 50 male and female were included respectively. Results: Significant (P≤0.05) changes in systolic and diastolic blood pressure were seen in the individuals of both groups regarding NaCl intake. The mean standard deviation levels, BMI, Systolic and Diastolic blood pressure of men in Group-A and Group-B in the beginning (27.03±0.02, 130.01±0.01, 90.01±0.02), (30.01±0.02, 135.01±0.01, 90.01±0.02) after 15 days (27.03±0.02, 125.01±0.01, 83.01±0.01), (30.01±0.02, 140.01±0.01, 90.01±0.02) and after30 days (27.03±0.02, 124.01±0.01, 80.01±0.01), (30.01±0.02, 145.01±0.01, 100.01±0.01) were measured respectively. Similarly the mean standard deviation levels, BMI, Systolic and Diastolic blood pressure of women in Group-A and Group B in the beginning (28.03±0.02, 131.01±0.01, 88.01±0.02), (31.02±0.02, 131.01±0.01, 88.01±0.02) after 15 days (28.03±0.02, 125.01±0.01, 83.01±0.01), (31.02±0.02, 140.01±0.01, 90.01±0.02) and after30 days (28.03±0.02, 120.01±0.01, 84.01±0.01), (31.02±0.02, 150.01±0.01, 92.01±0.01) were calculated. Conclusion: All recommendations suggest limiting dietary salt as one of the tried-and-true ways to lower high blood pressure because there is a well-established link between excessive salt consumption and hypertension. A current study proved that high sodium chloride intake may increase blood pressure in humans. Keywords: Hypertensive, Sodium Chloride, BMI, Systolic and Diastolic blood pressure.